Synchronization of estrus and ovulation in dairy heifers using norgestomet, GnRH, and PGF[subscript]2alpha - Stevenson, Jeffrey S.; Thompson, K. E.; Smith, John F., 1962-; Hawkins, D. E. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
Two experiments were performed using the same treatments. All heifers received two injections of PGF[subscript]2alpha 14 days apart. Controls then were inseminated after detected estrus. Heifers assigned to the two treatments also received 6 mg of norgestomet for 8 days beginning 7 days before the second of two PGF[subscript]2alpha injections. The heifers in the last treatment also received GnRH 48 hr after the second PGF[subscript]2alpha injection to induce ovulation in any heifer not observed in estrus before a fixed-time insemination at 72 hr after PGF2 alpha. In Experiment 1, any control heifer or herifer in the two treatments not detected in estrus by 72 hr after PGF[subscript]2alpha received a fixed-time insemination at 72 hr. Heifers receiving GnRH tended to have fewer standing events and a shorter duration of estrus. Fixed-time inseminations reduced conception compared to those after detected estrus. In Experiment 2, when inseminations were performed only after detected estrus, all measures of fertility were unaffected by treatments. These results indicated that addition of norgestomet and(or) GnRH did not improve measures of estrus synchronization or fertility of dairy heifers.
Keywords: Estrus synchronization; Standing estrus; Hormones; Heifers